Treatment of the interaction between polymers and liquids in terms of the linear free energies concept - Makitra, R.; Yevchuk, I.; Musiy, R. (Condensed Matter Physics, 2005)
The existing theories of interaction between polymers and liquids don’t reveal satisfactory relation between liquid physico-chemical properties and the degree of swelling of polymer in polymer-liquid system. We suggested the linear sixparametric equation, which takes into account both liquid capability of specific and nonspecific solvation and its cohesion energy and molar volume. This equation appears to be fit for treating the data within the processes such as: diffusion of liquids through the thin films, dissolution of polymers, swelling and extraction of coals.